Peran Inovasi Nama Produk dalam Penguatan Identitas UMKM Desa Ciranggem (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Many Micro, Small, and Medium Enterprises (MSMEs) in rural areas have strong economic potential but face marketing challenges due to the lack of clear brand identities. This issue was identified among MSME products in Ciranggem Village, Jatigede District, Sumedang Regency. This community service program aimed to improve MSME owners' understanding of product naming as a branding strategy and to strengthen product identity. The program adopted a qualitative participatory approach using Participatory Action Research (PAR). Data were collected through door-to-door observations, interviews, and MSME product mapping, followed by branding socialization, participatory discussions, and product naming assistance. The results showed that 6 out of 16 identified MSMEs did not have product names or brand identities. After the program, participants demonstrated a better understanding of the importance of branding and product naming in enhancing business identity and market appeal. The mentoring also produced several product name innovations, including "Gulcik," an acronym for Gula Cikandang. The program demonstrates that product naming and branding can strengthen product identity, improve competitiveness, and support the marketing of MSME products in Ciranggem Village.